Sistem Pendukung Keputusan Pemilihan Smartphone Menggunakan Metode Simple Multi Attribute Rating Technique Berbasis Web - Kelvin Benyamin Sitompul; Sariyun Naja Anwar (Fakultas Teknologi Informasi Universitas Kristen Satya Wacana, 2023)
Information Technology (IT) will always be present if discussed continuously. From day to day, IT is constantly overgrowing, focusing on helping meet human needs in various fields. One of them is the field of communication, namely smartphones. This article develops a web-based decision support system for selecting smartphones using Simple Multi-Attribute Rating Technique. The results obtained in this study produce decisions in the form of selecting smartphones based on smartphone data that has been collected, namely brands (Apple, Samsung, Xiaomi, Realme, and Oppo), price, operating system, ram, storage capacity, and battery. From the test results to determine ranking, the final value is 0.538, included in the best ranking category, so this system suits users. The resulting smartphone selection system can be used to simplify and speed up the determination process.